Natural variation in physiological traits in a large panel of brazilian Capsicum chinense acessions - Souza, Laíse Rosado de (2013)
Diversity of accessions within the same specie has been reported as an alternative way to search for physiological and metabolic traits that may have large effects on both growth regulation and biomass production. This work aimed to investigate physiological and metabolic traits as well as its interactions with plant growth and fruit production using 49 genetically diverse brazilian pepper accessions of Capsicum chinense. These different accessions were grown together and genetic variation was observed for many traits. Although the analysis of each variable individually allowed the formation of up to seven distinct groups, as observed for plant height, working with the whole data set by multivariate analyzes allowed the separation of the 49 accessions in only three clusters. Interestingly, the groups formed by this analysis did not follow the geographical origin of the genotypes. The first cluster contains two accessions with lower plant height and relative growth rate (RGR). On the other hand, the same accessions had the highest specific leaf area (SLA), high photosynthesis rates and have the highest nitrate (NO 3 ) content. Genotypes in the second cluster demonstrate opposite behavior for growth parameters and NO 3, however they had an undefined pattern for gas exchange parameters and water use efficiency (WUE), despite having low values of SLA. The third cluster comprised the other accessions with the most diverse results for the investigated characteristics. Altogether, these results reinforce the idea that, although the accessions belong to the same species, they have diverse adaptation mechanisms being a highly interesting source of information for plant breeders. In addition, it was demonstrated that fruit set is positively correlated with photosynthesis. However, photosynthesis does not explain alone the differences in accession susceptibility to fruit abortion. Metabolite analysis revealed that malate and fumarate had different responses in Capsicum. Although fumarate did not individually contribute to the accession group separation, a large number of significant correlations was observed. In summary the results obtained suggest fumarate as an important metabolite that might be involved in the regulation of both shoot and fruit growth and development of C. chinense. Apart from extending our knowledge of biological mechanism and pathways within the Capsicum genus the work presented here highlights the importance of studying genetic variation as a mean to understand how a specie adapts to different local environments.